Proceedings of the IFPRI/FAO Workshop on Plant Nutrient Management, Food Security, and Sustainable Agriculture: The Future Through 2020, Viterbo, Italy, May 16-17, 1995. - Gruhn, Peter; Goletti, Francesco; Roy, Rabindra N. (International Food Policy Research Institute, 1998)
In the next 25 years, the challenge for agriculture will not only be to meet the food needs of Earth's expanding population, but also undertake it in a manner that is sustainable for present and future generations. The challenge for agriculture is immense. By 2020, the population of Earth is projected to approach eight billion, an increase of some 2.3 billion from 1995. Although world population growth rates will slow and approach zero in the more developed regions, population growth is projected to increase by over two percent in Africa and just under one percent in Asia around the year 2020. Already during the early 1990s, 95 percent of world population growth occurred in the less developed regions (United Nations 1993, United Nations 1995). Baseline projections by the International Food Policy Research Institute (IFPRI) indicate that world cereal production will need to expand to 2.6 billion tons by 2020, an increase of 56 percent from production levels in 1990. The majority of the increase in world cereal production growth is projected to occur in developing countries, with cereal production forecast to rise by 70 percent in Asia and by 140 percent in Sub-Saharan Africa (Rosegrant et al 1995). As land constraints become increasingly binding, the synergy generated by genetic engineering and plant nutrients will be necessary to maintain and boost crop yields.